Effective hydroconversion of heteroatom-containing organic species from the extraction of low-temperature coal tar to cycloalkanes over a Y/Beta composite zeolite supported nickel nanoparticles. (1st August 2022) - Zhang, Xiao-Qi; Kang, Yu-Hong; Gao, Juan; Xiong, Lei; Gao, Yong; Chen, Tao; Liu, Guang-Hui; Wang, Ai-Min; Wei, Xian-Yong; Zong, Zhi-Min; Bai, Hong-Cun
Highlights: HACOSs in EPCDS from LTCT are effectively separated by successive solvent extraction. Ni10% /YBCZ has an outstanding catalytic activity for the CHC of EPCDS . Ni10% /YBCZ efficiently induced the formation of H +, H -, and H … H during the CHC. All of group components in EPCDS were completely converted to cycloalkanes and hydroarenes. Abstract: The preparation of high activity bifunctional catalysts, especially hierarchical porous zeolite-supported metal catalysts, are of great important for efficient converting the heteroatom-containing organic species to high quality clean fuels. An excellent performance Ni catalyst was prepared by loading highly dispersed Ni nanoparticles (NNPs, ca . 10%) on Y/Beta composite zeolite (YBCZ) and denoted as Ni10% /YBCZ. Low-temperature coal tar was efficiently extracted with petroleum ether, methanol, and carbon disulfide (CDS) at room temperature under ultrasonic irradiation to obtain CDS extractable portion (EPCDS ) in the yield of 20.1%. According to the analysis with a GC/MS, EPCDS consists of chain alkanes (CAs, 4.0%), oxygen-containing organic compounds (OCOCs, 56.0%), arenes (35.3%), nitrogen-containing organic compounds (NCOCs, 3.3%), and sulfur-containing organic compounds (SCOCs, 1.4%). It was subjected to catalytic hydroconversion (CHC) over Ni10% /YBCZ at 160 °C for 18 h under 5 MPa of initial hydrogen pressure to obtain EPCHC . The results show that all organic species in EPCDS were completely converted to CAs (9.0%), cycloalkanes (70.8%), and hydroarenes (20.2%). In Ni10% /YBCZ, hierarchical porous zeolite-zeolite composite with strong Lewis acid sites in its crystal texture and highly dispersed NNPs play crucial roles in removing heteroatoms and hydrogenating aromatic rings, respectively. Oxydibenzene, a model compound with > Car -O bridge bonds and aromatic rings, was used to investigate the catalytic activity of Ni10% /YBCZ. Oxydibenzene was effectively converted to cyclohexane, bicyclohexane, and tercyclohexane over Ni10% /YBCZ in n -pentane at 160 °C for 2 h under 5 MPa of initial hydrogen pressure, indicating that Ni10% /YBCZ has excellent activity in CHC process under mild conditions.